2021
DOI: 10.1007/s12559-021-09885-y
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis and Forecasting of the COVID-19 Spread: A Comparison of Recurrent Neural Networks and Time Series Models

Abstract: To understand and approach the spread of the SARS-CoV-2 epidemic, machine learning offers fundamental tools. This study presents the use of machine learning techniques for projecting COVID-19 infections and deaths in Mexico. The research has three main objectives: first, to identify which function adjusts the best to the infected population growth in Mexico; second, to determine the feature importance of climate and mobility; third, to compare the results of a traditional time series statistical model with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…For instance, some studies forecasted cumulative confirmed cases 29 or cumulative vaccination rates 30 using past observations. Other studies used predictor variables including temperature, mobility, and social distancing 26 , 27 . However, these studies only compare the prediction models, not predictor variables 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies forecasted cumulative confirmed cases 29 or cumulative vaccination rates 30 using past observations. Other studies used predictor variables including temperature, mobility, and social distancing 26 , 27 . However, these studies only compare the prediction models, not predictor variables 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A su vez, la combinación de métodos de aprendizaje automatizado con modelos tradicionales arima y de crecimiento ha sido empleada para modelar la expansión de contagios en México y otros países, como es el análisis de Naemi et al (2022), en donde se analizan los brotes de covid-19 utilizando modelos híbridos. Asimismo, el análisis de Gómez-Cravioto et al (2022) para predecir picos de contagios se basa en modelos de series de tiempo, específicamente en Vectores Autorregresivos (var) combinados con una especificación de red neuronal autorregresiva (Long Short-Term Memory, lstm, por sus siglas en inglés), propuesto por Hochreiter y Schmidhuber (1997), mismos a que vez pertenecen a los modelos de aprendizaje profundo.…”
Section: Metodologías Propuestas Para Modelar El Covid-19unclassified
“… Brazil, France, India, Mexico, Russia, Saudi Arabia, the US; Jan - Sep, 2020 0.63 - 6.02. Gomez et al, 2021 [28] Compared univariate population growth models, VAR, and M-LSTM and found that the M-LSTM model achieved the lowest errors. Mexico; Jan - Mar, 2020 0.47 Kafieh et al, 2021 [41] Compared RF, MLP, LSTM-R, LSTM-E, M-LSTM models and found that M-LSTM achieved the smallest error.…”
Section: Deep Learning Models For Covid-19 Forecastingmentioning
confidence: 99%